The Influence of Halal Awareness and Halal Certificate on Purchasing Decisions for Mixue Products - Muhammad Ilham Atha Abhinaya; Anton Agus Setyawan (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to analyze the effect of halal awareness and halal certificate on purchasing decisions for Mixue products. This type of research is quantitative. The population of this study were students of Universitas Muhammadiyah Surakarta. The sample calculation technique using the malhorta formula, obtained a sample size of 100 respondents. Non-probability sampling design with purpose sampling technique is used to take samples carried out in research. The data source of this research is primary data. The method of data analysis in this study with the help of the SPSS application. The result of this study is that there is an effect of Halal Awareness on purchasing decisions. Halal Certificate has a positive and significant effect on purchasing decisions. This shows that students at Universitas Muhammadiyah Surakarta really consider Halal Awareness and Halal Certificate in consuming a product. A consumer's awareness of halal products is one of them by knowing the food packaging process used, the cleanliness of the food they consume. This is important to ensure that the products they consume are truly halal products.